2020
DOI: 10.1088/1361-6501/ab8170
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurement and evaluation of flatness error for the aero-engine rotor connection surface based on convex hull theory and an improved PSO algorithm

Abstract: The precision measurement and evaluation of the geometry form error for high-end precision components is one of the most important tasks for metrologists. In this paper, a novel hybrid flatness error evaluation method is proposed to measure and evaluate the flatness error for large-scale point cloud data. This method is based on the convex hull algorithm and the improved particle swarm optimization (IPSO) algorithm. Not only are a large number of redundant measurement data points effectively removed through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the particle swarm algorithm model, each particle's own state is described by a set of position and velocity vectors representing the feasible solution of the problem and its direction of motion in the search space. (27) The particle follows the global optimal search by continuously learning and comparing the group and neighbor optimal solutions. The particle velocity and position update equations are the core of the PSO algorithm and are described by…”
Section: Mathematical Model Of Flatnessmentioning
confidence: 99%
“…In the particle swarm algorithm model, each particle's own state is described by a set of position and velocity vectors representing the feasible solution of the problem and its direction of motion in the search space. (27) The particle follows the global optimal search by continuously learning and comparing the group and neighbor optimal solutions. The particle velocity and position update equations are the core of the PSO algorithm and are described by…”
Section: Mathematical Model Of Flatnessmentioning
confidence: 99%
“…Many studies have shown that the inertia weight should be larger in the global phase but smaller in the local stage of determining the exact location of the optimal solution. 34,35 However, the inertia weight of standard PSO algorithm is linear decreasing, which is simple and intuitive, but it is easy to fall into local optimum, so this paper uses nonlinear decreasing strategy instead of linear strategy. The specific implementation formula is as follows.…”
Section: Improved Pso Algorithmmentioning
confidence: 99%
“…In PSO algorithm, the inertia weight plays an important role in maintaining the inertia of particle motion and balancing the global search and local search ability of the algorithm, which greatly affects the convergence speed of the algorithm. Many studies have shown that the inertia weight should be larger in the global phase but smaller in the local stage of determining the exact location of the optimal solution 34,35 . However, the inertia weight of standard PSO algorithm is linear decreasing, which is simple and intuitive, but it is easy to fall into local optimum, so this paper uses nonlinear decreasing strategy instead of linear strategy.…”
Section: Improved Pso Optimized Adaptive Volterra Filtermentioning
confidence: 99%
“…Aero-engine assembly is the last part of the aero-engine manufacturing process, and its assembly quality will directly affect the performance, reliability, and life of the aero-engine [1][2][3][4][5], and the poor assembly may lead to serious vibration or even collision when the rotor rotates at high speed, which is related to the stable operation and safety of the aviation system [6][7][8][9]. The multi-stage rotors in aero-engines are cylindrical components of the rotary symmetry class, and there is a problem of gradual accumulation of machining errors of rotors at all levels during the assembly process [10][11][12], so the precision measurement of single-stage rotor circular contours is a prerequisite and basis for ensuring the rationality of the assembly process.…”
Section: Introductionmentioning
confidence: 99%